Medication wastage and its impact on environment: evidence from Malaysia - Islam, Mohd Aminul; Azad, Abul Kalam; Hossin, M.M; Muhammad, K.R.; Robiul, Islam; Abdullahi, M.M (Societa Italo-Latinoamericana di Etnomedicina (SILAE), 2016)
The purpose of this study is to investigate the critical factors that have impact on environment causes of unused medication. The current study is a descriptive cross-sectional audit involving with patients based on a structured questionnaire format with answer sets. The data is analyzed using partial least square method. The results revealed that excess supplied, expired medicine, changed treatment and side effects have a significant impact on unused medication. In addition, overall unused medication has a significant relationship with environmental effect. In contrast, although excess supplied and side effects have not significant impact on environmental effect, but expired medicine and changed treatment have a significant impact on environmental effect. This survey results suggested; there are few factors which increased the volume of leftover medicine and it has led to an enhanced international awareness of the potential detrimental effects on the environment. More exertion is necessary to raise awareness of people in general as an initial step in promoting behavioral change in connection to medication wastage.